2006
DOI: 10.1111/j.1467-789x.2006.00251.x
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal disorders associated with obesity: a biomechanical perspective

Abstract: Despite the multifactorial nature of musculoskeletal disease, obesity consistently emerges as a key and potentially modifiable risk factor in the onset and progression of musculoskeletal conditions of the hip, knee, ankle, foot and shoulder. To date, the majority of research has focused on the impact of obesity on bone and joint disorders, such as the risk of fracture and osteoarthritis. However, emerging evidence indicates that obesity may also have a profound effect on soft-tissue structures, such as tendon,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
256
0
26

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 391 publications
(293 citation statements)
references
References 204 publications
(223 reference statements)
11
256
0
26
Order By: Relevance
“…Similar to previously published researches, women population has a higher prevalence of MSK pain compared to men [1][2][3]. The most prevalent painful sites were lower back, upper back, and neck respectively.…”
Section: Discussion:-supporting
confidence: 75%
“…Similar to previously published researches, women population has a higher prevalence of MSK pain compared to men [1][2][3]. The most prevalent painful sites were lower back, upper back, and neck respectively.…”
Section: Discussion:-supporting
confidence: 75%
“…Obesity consistently emerges as a key and potentially modifiable risk factor in the onset and progression of musculoskeletal conditions and pain (Wearing et al, 2006), which in its turn impairs the ability to perform weightbearing activities such as walking. Previous research demonstrated that people with bipolar disorder with a higher BMI indeed experience more foot or ankle problems and back pain, which impairs the ability to perform daily life activities .…”
Section: General Findingsmentioning
confidence: 99%
“…[132][133] However, the observed hormonal changes could be more speculative and influenced by the obesity status. 134,135 In weight-bearing activities, the weight of the obese child might increase the risk of musculoskeletal disorders. 134 In comparison with normotensives, hypertensive children can have an Hyperkalemia, hypotension, renal failure, angioedema, gastrointestinal side effects, cough.…”
Section: Pa As a Drug: Its Use Effects And Limitsmentioning
confidence: 99%
“…134,135 In weight-bearing activities, the weight of the obese child might increase the risk of musculoskeletal disorders. 134 In comparison with normotensives, hypertensive children can have an Hyperkalemia, hypotension, renal failure, angioedema, gastrointestinal side effects, cough. Four options: X, when established effect; x, when minimal effect; ?, when questionable effect; F, no effect.…”
Section: Pa As a Drug: Its Use Effects And Limitsmentioning
confidence: 99%